Oxidative charge transfer of EMFs, biomedical applications of EMFs, and EMF-based nanomaterials and molecular materials - Lederer, Marcus; Rudolf, Marc; Wolf, Maximilian; Guldi, Dirk Michael; Zhao, Shasha; Lu, Xing; Feng, Lai (CRC Press, 2014)
Fullerenes have been under investigation in different fields of research for nearly 30 years. In September 1985, a group of scientists including Robert Curl, James Heath, Harry Kroto, Yuan Liu, Sean O’Brian, and Richard Smalley discovered fullerenes via mass spectrometry at Rice University in Houston, Texas [1]. This new class of carbon allotropes was termed buckminsterfullerenes because the geodesic domes designed by inventor and architect Buckminster Fuller provided a decisive clue about their structure (Figure 7.1) [2]. A decade later, namely, in 1996, Curl, Kroto, and Smalley were awarded with the Nobel Prize in chemistry for the discovery of fullerenes [1].
CRIS-Team Scopus Importer:2023-03-07